Methane Seeps and Independent Methane Plumes in the South China Sea Offshore Taiwan - Mau, Susan; Tu, Tzu-Hsuan; Becker, Marius; dos Santos Ferreira, Christian; Chen, Jhen-Nien; Lin, Li-Hung; Wang, Pei-Ling; Lin, Saulwood; Bohrmann, Gerhard (Frontiers in Marine Science, 2020)
In the northern South China Sea (SCS) we explored methane dynamics in the water column during SONNE-cruise SO266 in October/November 2018. Two depth zones contained elevated methane concentrations: the upper 400 m (< 10 nM) and near gas seeps at the seafloor (up to 2100 nM). Seeps occurred at Four Way Closure Ridge (FWCR) at the active continental margin as well as at Southern Summit Formosa Ridge (SSFR) at the passive continental margin. In the upper ocean, methane dynamics correlated with (1) temperature, (2) water masses, and (3) suspended matter. In the first case, elevated methane concentrations and aerobic methane oxidation rates occurred in water with temperatures > 10°C and > 20°C, respectively. Both 16S rRNA gene and pmoA amplicon analyses revealed distinct microbial and methanotrophic communities in water with temperature of 27°C, 10°C, and 3°C. Second, we found elevated methane concentrations in 200-400 m in the FWCR-region whereas increased methane concentrations occurred in the uppermost 100 m above SSFR. The deeper plume above FWCR might be due to an intrusion of the Kuroshio water mass into SCS keeping the methane from being aerobically oxidized in the warm surface water and vented to the atmosphere. Finally, all peak methane concentrations occurred in water depth, with rather low backscatter, i.e. in water depth with less suspended matter. At the seafloor, ocean currents and long-term seepage appeared to control methane dynamics. We derived methane fluxes of 0.08-0.12 mmol m-2 d-1 from a 4.5 km2 area at FWCR and of 3.0-79.9 mmol m-2 d-1 from a 0.01 km2 area at SSFR. Repetitive sampling of the area at SSFR indicated that changing directions of ocean currents possibly affected methane concentrations and thus flux. In contrast to these seepage sites with distinct methane plumes, retrieval of drilling equipment produced no methane plume. Even gas emission triggered by seafloor drilling did not supply measureable methane concentrations after 3 hours, but caused an increase in methanotrophic activity as determined by rate measurements and molecular-biological analyses. Apparently, only long-term seepage can generate methane anomalies in the ocean.